Pelaksanaan Kebijakan Pembangunan Kawasan Khusus Pariwisata Di Kabupaten Kepulauan Sula Provinsi Maluku Utara Tahun 2014 - Buamona, Darwawan; Pribadi, Ulung (Journal of Governance and Public Policy, 2015)
Natural resources and biodiversity Indonesia make this country rich with potential that exists in it, the main challengeis how to both the way the government manages the resources and can be functioned as it should be for the State andthe Regions. Through the Regional Autonomy in Regions expected to be more independent in determining the wholethe activity as a subordinate of the Unitary Republic of Indonesia, Sula Islands Regional Government also has the samelegitimacy to make various policies, including in the field of tourism. Sula Islands Government has set as part of thedevelopment of tourism and economic make-Based Tourism Policy development to support the development of tourism.Sulabesi island Sula Islands has five locations coastal tourist potential to be developed as a regional destinationtour namely Wai ipa of beach, Pagama Island, Coastal Fatkauyon, Goiyofa Wai of beach,and pas ipa of beach. TourismRegions Island Beach Sulabesi have a characteristic of a typical and natural. But not yet supported by facilities andinfrastructure, including tourist facilities are good and decent for tourists.This research was conducted using qualitativeresearch methods with fenomenalogi approach to describe, analyze and interpret the sides of policies such asparticipation, networking, Organizational Structure, actor, financial, facilities, social, cultural, economic and political aswell as the interests of stakeholders.The results showed that the availability of resources have not been allocated tosupport the implementation of clear, communication and coordination has not run optimally, external conditions (social,economic, and political) impede the implementation of special regional development policy implementation in SulaIslands tourism effectively and optimally. The implication is activity-based tourism economy has not contributed optimallyto the government, private and community from an economic standpoint.